High power fiber laser - Li, Dong Rui. (2010)
This report pertains to study and features, properties study and experiment of fiber laser and its performance. As knowledge preparation, the knowledge of background study will be generally included in the introduction part. Some focus will also be put into the study of features and mechanisms of the laser component and different cavity structures. The test and measurement of laser component will be covered in Chapter 3, where the testing device, the component to be tested and the parameter that should be focused on is also discussed. Chapter 4 and Chapter 5 are about the fiber laser setup, experiment, modification attempt and analysis on the results. In the two chapters, Chapter 4 focus on ring cavity with both EDF (Erbium-doped fiber) and YDF (Ytterbium-doped fiber) doped fiber will be talked about. In Chapter 5, the focus is put on linear cavity and EDF and YDF are also both used as gain medium. Comparing the result between Chapter 4 and 5, the conclusion and recommendation gives the conclusion of successful points, reasons to the bad results and the aspects that need to be improved are also recommended.